Cash Flow and Discount Rate Risk in Up and Down Markets: What Is Actually Priced? - Botshekan, Mahmoud; Kraeussl, Roman; Lucas, Andre (Journal of Financial and Quantitative Analysis, 2012)
Abstract We test whether asymmetric preferences for losses versus gains affect the prices of cash flow versus discount rate risk. We construct a return decomposition distinguishing cash flow and discount rate betas in up and down markets. Using U.S. data, we find that downside cash flow and discount rate betas carry the largest premia. Downside cash flow risk is priced consistently across different samples, periods, and return decomposition methods. It is the only component of beta with significant out-of-sample predictive ability. Downside cash flow premia mainly occur for small stocks, while large stocks are compensated for symmetric cash-flow-related risk.